First steps to integrate general palliative care into a cardiac hospital setting – using dialogue‐based workshops. Issue 1 (3rd March 2021) - Roikjær, Stine Gundtoft; Timm, Helle; Simonÿ, Charlotte
Abstract: Background: Heart failure is a chronic, life‐threatening illness with multiple acute events. Palliative care alongside standard treatment is recommended for these patients. There is a lack of knowledge and research literature on how to integrate palliative care interventions for heart failure patients in a general hospital setting. Aim: The aim of this study was to produce new insight for developing and integrating general palliative care into heart failure treatment. Methods: Guided by action research, we conducted an interdisciplinary workshop inspired by Tsoukas dialogue theory, where tension between perspectives is used as a facilitator of dialogue and the generation of new insights. Perspectives were incorporated through selected patient narratives and professionals' experiences. Data from the workshop were analysed using a thematic analysis. The findings are interpreted with Kleinman's theory on illness and disease and discussed using Tsoukas theory and additional research. Results: General palliative care must be initiated from the patient's perspective and wishes. Doing so requires understanding and uniting the different perspectives and objectives of heart failure treatment and palliative care. One way of doing this is through a narrative approach with interdisciplinary teams. However, this requires organisational efforts and adaptation to the specific cardiac setting. Conclusion: Integrating palliative care principles into cardiology is a complex issue. Developing palliative care for heart failure patients requires more than simply designing a set of guidelines. Rather, a wider outlook involving perspectives, competences and organisation is necessary. Acknowledging such considerations, we designed an intervention centred on three elements: standard heart failure treatment, integrated sessions applying a narrative approach and monthly interdisciplinary conferences. Relevance: This article adds to the current research literature on changing palliative care practice for heart failure patients and the value of integrating different perspectives.